Bioinformatics in the identification of microorganisms - Yeoh, Chiann Ying; Cheah, Yoke Kqueen (Life Sciences, Medicine and Biomedicine, 2020)
Rapid and accurate identification of microorganisms can be of great value for clinical management. For many fastidious and slow-growing microorganisms, the conventional method used for detection is time-consuming, costly and labour-intensive. Hence, the development of new and improved microbial identification methods are necessary to overcome this bottleneck. Current trend has shifted towards the use of new molecular technologies in genomics and proteomics for bacterial identification and characterization. This mini review will focus on summarizing different types of genotypic and proteomics identification methods, as well as bioinformatics tools used for rapid identification and characterization of microorganisms from various specimens.